In Silico and In Vivo Studies of Decursin Isolated From the Ethanolic Extract of Feronia elephantum Correa (Rutaceae) Bark as a Potential Antidiabetic and Antihyperlipidemic Agents in STZ-induced Diabetic Rats - Vikhe, Sunayana; Kunkulol, Rahul; Raut, Dipak (Letters in Drug Design & Discovery, 2023)
Background: Feronia elephantum (Rutaceae), frequently named wood apple, is a preferable medicinal plant. In Ayurveda, its bark has been recommended for treating diabetes. In addition, it is one of the active chemical constituents, decursin, shown in recent research to significantly impact colon cancer, breast cancer, Alzheimer's disease, inflammation, and ulcerative colitis. Objective: The present study was carried out to investigate the traditional use of Feronia elephantum bark in streptozotocin-induced diabetes and lipid-lowering action in rats. Decursin has been isolated from the bark and tested for in vitro and in vivo biological activities. Methods: The Soxhlet extraction method obtained the ethanolic extract, and fractionation was done with column chromatography and TLC. The structure of isolated decursin has been confirmed by Fourier transform infrared (FTIR) and nuclear magnetic resonance (NMR) spectroscopy. Results: The decursin noticeably depletes increased blood glucose levels and positively affects altered lipid profiles after administering a dose of 150 mg/kg orally compared with the hypoglycemic drug metformin. In molecular docking simulations, decursin exhibited excellent inhibition of α-amylase, dipeptidyl peptidase-IV, and moderate activity against α-glucosidase and glucokinase. Furthermore, the enzymes 3- hydroxy-3-methylglutaryl coenzyme A and Niemann-Pick C1-Like 1 are ideal targets to control hyperlipidemia and have shown moderate inhibition by decursin. Conclusion: From these results, it has been concluded that decursin is the perfect candidate for further optimization as a lead molecule to treat diabetes and hyperlipidemia.
Keywords: α-glucosidase